Carp horizontal cells in culture respond selectively to L-glutamate and its agonists. - Lasater, E M (1982)
Horizontal cells were enzymatically isolated from the carp retina and maintained in culture for 2-7 days. Cultured horizontal cells typically had resting membrane potentials of -50 to -70 mV and input resistances of 100-150 m omega. The cells were treated with a number of neurotransmitter agents and their analogues. Significant responses were evoked only by 3,4-dihydroxyphenylalanine (dopamine), L-glutamate, and certain glutamate analogues. The responses to dopamine were inconsistent; most often, the membrane hyperpolarized and input resistances increased. However, highly characteristic responses to L-glutamate and its analogues, quisqualate and kainate, were observed in virtually all of the cells tested. The responses consisted of an initial graded depolarization accompanied by a resistance increase, followed in most cases by a prolonged (1- to 2-min) regenerative depolarization. The regenerative component of the response appears to be Ca2+ dependent, while the underlying graded potential may be due to a decrease in K+ conductance of the membrane.